IN VITRO ACTIVITY OF LINEZOLID AGAINST CLINICAL ISOLATES OF METHICILLIN RESISTANT STAPHYLOCOCCUS - Hannan, Abdul; Absar, Muhammad; Usman, Muhammad; Naeem, Tahir; Saleem, Sidrah; Arshad, Muhammad (Journal of Ayub Medical College Abbottabad, 2009)
Background: Staphylococcus is responsible for a variety of medical problems, including skin and softtissue infections (SSTIs), surgical site infections (SSIs), endocarditis and hospital acquired bacteraemia. Methicillin resistance in staphylococcus has become a global problem limiting the treatment modalities to a large extent. Methods: The aim of this study was to evaluate the in vitro activity of linezolid and other antibiotics against clinical isolates of methicillin resistant staphylococcus (n=163); including 105 methicillin resistant Staphylococcus aureus and 58 methicillin resistant coagulase negative staphylococci. Antibiogram of these isolates was determined by the Kirby-Bauer disc diffusion method and minimum inhibitory concentration of linezolid was determined by standard agar dilution method. Results: Overall methicillin resistant S. aureus showed high multi-drug resistance. ATCC 25923 Staphylococcus aureus and ATCC 29213 Staphylococcus aureus were used as the standard control strains. MIC90 of linezolid was comparable for methicillin resistant coagulase negative staphylococci and methicillin resistant S. Aureus (4.0 mg/L); however at MIC50 linezolid was two fold more active against methicillin resistant coagulase negative staphylococci (1mg/L) than methicillin resistant S. aureus (2mg/L). Conclusion: It is concluded that linezolid has excellent activity against methicillin resistant staphylococci including multidrug resistant strains. Keywords: Linezolid, MIC, MRSA, MRCoNS